Penerapan Stretegi Manajemen Konflik Dalam Tim Kerja - Anisyah Rahmadani; Agus Wahyudi; Ajeng Rizqi Marwaty; Maghfur Maghfur (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Conflict is an inseparable part of human life, including in organizations within companies, which often arises in various conditions. Conflict, although it occurs very often, requires proper understanding and handling so as not to hamper company activities. Good conflict management can not only prevent negative impacts, but also open up opportunities for introspection and improving team performance. This research examines strategies for implementing conflict management in work teams, with a focus on how company organizational leaders play an important role in managing conflict effectively. The research results show that well-managed conflict can strengthen teamwork, increase productivity, and create a more harmonious work environment. On the other hand, conflicts that are not handled well can have a negative impact on the continuity of the company. Strategies such as open communication, mediation, and approaches to decision making are very effective in work team conflict management